A review on antifungal activity of mushroom (basidiomycetes) extracts and isolated compounds - Alves, Maria José; Ferreira, Isabel C F R; Dias, Joana; Teixeira, Vânia; Martins, Anabela; Pintado, Manuela (Current topics in medicinal chemistry, 2013)
The present review reports the antifungal activity of mushroom extracts and isolated compounds including high (e.g. peptides and proteins) and low (e.g. sesquiterpenes and other terpenes, steroids, organic acids, acylcyclopentenediones and quinolines) molecular weight compounds. Most of the studies available on literature focused on screening of antifungal activity of mushroom extracts, rather than of isolated compounds. Data indicate that mushroom extracts are mainly tested against different Candida species, while mushroom compounds are mostly tested upon other fungi. Therefore, the potential of these compounds might be more useful in food industry than in clinics. Oudemansiella canarii and Agaricus bisporus methanolic extracts proved to be the most active mushroom extracts against Candida spp. Grifolin, isolated from Albatrellus dispansus, seemed to be the most active compound against phytopathogenic fungi. Further studies should be performed in order to better understand the mechanism of action of this and other antifungal compounds as well as safety issues.